Impact of Online Learning Platforms on Student Engagement in India - Joshi, Divya (International Journal of Online and Distance Learning, 2024)
Purpose: The aim of the study was to investigate the impact of online learning platforms on student engagement in India. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Research on online learning platforms in India highlights increased access to education, particularly in remote areas. Students show high engagement due to platform convenience and interactive features. Challenges like the digital divide impact equitable access and engagement. Despite these challenges, online platforms have the potential to revolutionize education in India. Addressing accessibility barriers is crucial for maximizing engagement and ensuring inclusive learning. Unique Contribution to Theory, Practice and Policy: Social presence theory, cognitive load theory & technology acceptance model (TAM) effect may be used to anchor future studies on the impact of online learning platforms on student engagement in India. Pedagogical Innovation and Teacher Training - Educational institutions in India should prioritize pedagogical innovation and invest in teacher training programs focused on effective online instruction. Digital Infrastructure and Accessibility - Policymakers must address infrastructural challenges and promote equitable access to digital resources and connectivity across all regions of India.